Laparoscopic partial splenectomy for traumatic splenic rupture patients is safe and feasible - Xu, Jingna; Zhou, Weiguang; He, Qiang; Tao, Liang (Frontiers in Surgery, 2025)
BackgroundTraumatic splenic rupture is a life-threatening acute abdominal condition. While traditional total splenectomy effectively controls bleeding, it results in the loss of splenic function, increasing the risk of infectious complications and long-term health issues. Laparoscopic partial splenectomy, as a minimally invasive spleen-preserving approach, offers a new treatment option for such patients. However, its technical complexity limits its clinical adoption, requiring further experience accumulation and technical optimization.MethodsThis study retrospectively analyzed the clinical data of 13 patients with traumatic splenic rupture treated between 2018 and 2021 to evaluate the safety, efficacy, and applicability of laparoscopic partial splenectomy. All patients were diagnosed via contrast-enhanced abdominal CT imaging. During surgery, partial splenectomy was performed using splenic artery occlusion combined with anatomical dissection. Perioperative data and postoperative changes in blood parameters were recorded.ResultsThe median operative time was 120 min, with a median intraoperative blood loss of 1,500 mL. The residual spleen in all 13 patients maintained good blood supply. Blood tests showed a gradual resolution of postoperative inflammatory responses, with platelet levels returning to normal. Imaging follow-up confirmed improved blood supply to the residual spleen. The median postoperative hospital stay was 14 days, and all patients survived and preserved splenic tissue. One patient developed a minor splenic infarction that resolved, and no patient experienced re-bleeding, overwhelming infection, or other major complications.ConclusionsLaparoscopic partial splenectomy demonstrates favorable safety and efficacy in patients with traumatic splenic rupture. By optimizing intraoperative vascular control and careful management of the resection site, this procedure not only preserves partial splenic function but also reduces postoperative complications. It provides a reliable minimally invasive surgical option for the treatment of traumatic splenic rupture.